Learning over tea! Studying in informal learning spaces. Issue 1 (7th January 2014) - Hunter, Jonathan; Cox, Andrew
Abstract : Purpose: – The purpose of this paper is to offer an exploratory investigation of students' use of informal learning spaces for their studies at the University of Sheffield. Previous research has mainly focused on formal learning spaces such as libraries and lecture theatres, but there is an increasing recognition of the value of informal learning spaces such as coffee bars. Design/methodology/approach: – Questionnaires, observations and interviews were the sources of data for the study. The research approach particularly looked at how students used informal learning spaces and what their perceptions of the spaces were. Findings: – Analysis showed that students found that the background atmosphere greatly influenced their choice of study location and that technological devices were only used sparingly. Students adapted their study habits to fit the learning spaces that they liked. Originality/value: – Although, attention is often paid to the furniture and colour schemes in libraries, this article makes librarians consider the importance of all sensual stimuli in making libraries warm, friendly and homely spaces. The "Model of Zengagement" was developed to show how stimuli from the background atmosphere influences' students' study experience.